2020
DOI: 10.3390/antiox9070602
|View full text |Cite
|
Sign up to set email alerts
|

Olive Mill Wastewater Polyphenol-Enriched Fractions by Integrated Membrane Process: A Promising Source of Antioxidant, Hypolipidemic and Hypoglycaemic Compounds

Abstract: The valorisation of food wastes is a challenging opportunity for the green, sustainable, and competitive development of industry. The recovery of phenols contributes to the sustainability of olive waste sector, reducing its environmental impact and promoting the development of innovative formulations of interest for pharmaceutical, nutraceutical, and cosmeceutical applications. In this work, olive mill wastewater was treated through a combination of microfiltration (MF), nanofiltration (NF), and revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…In vitro and in vivo investigations have shown few ethnopharmaceutical activities, including antioxidative, anti-inflammatory, and anti-neoplastic effects. 23,25,[51][52][53] Therefore, the present study revealed, for the first time, the beneficial health effects of LUT against DOX-induced oxido-inflammatory responses in the reproductive organs of male Wistar albino rats. Rats exposed to DOX exhibited marked (p < 0.05) diminutions in the mean body weight, thus indicating general toxicity and alterations of metabolic functions.…”
Section: Discussionmentioning
confidence: 88%
“…In vitro and in vivo investigations have shown few ethnopharmaceutical activities, including antioxidative, anti-inflammatory, and anti-neoplastic effects. 23,25,[51][52][53] Therefore, the present study revealed, for the first time, the beneficial health effects of LUT against DOX-induced oxido-inflammatory responses in the reproductive organs of male Wistar albino rats. Rats exposed to DOX exhibited marked (p < 0.05) diminutions in the mean body weight, thus indicating general toxicity and alterations of metabolic functions.…”
Section: Discussionmentioning
confidence: 88%
“…In the previous work, Tundis et al [ 19 ] investigated a combination of pressure-driven membrane operations in a sequential design to produce a polyphenol-enriched fraction from the same OMW sample used in this study. OMW was microfiltered and submitted through NF and RO steps to concentrate phenolic compounds up to volume reduction factors of 4 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This process allowed reducing the suspended solids content from 11.5% to 2.0%. Pre-treated OMW was submitted to a microfiltration process by using a pilot unit equipped with a multichannel ceramic (TiO 2 ) membrane (Ceram Inside, from Tami Industries, nominal pore size of 0.1 μm, and membrane surface area of 0.35 m 2 ), according to the procedure reported by Tundis et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another integration scheme relied on the direct use of RO instead or in addition to the NF. Tundis et al [ 33 ] showed the recovery and classification of polyphenols by using a MF step on a 0.1 µm TiO 2 membrane followed by a NF step and a RO step based on a membrane typically applied to brackish water. Although a flux decay was observed for all the membrane filtrations, as the aim of the work was about the characterization of the polyphenols in the concentrate, the quality of the final NF and RO permeates was not assessed by the authors.…”
Section: Introductionmentioning
confidence: 99%